Sosialisasi Penerapan Building Information Modeling (BIM) sebagai Upaya Peningkatan Kompetensi Digital Konstruksi pada Siswa SMK4 Tangerang - Era Agita Kabdiyono; Jalaludin Jalaludin; Dedi Prihadi; Rosario; Naufal Dwi Aryo Prasojo (Jurnal Abdi Masyarakat Multidisiplin, 2026)
The rapid development of digital technology in the construction industry demands the improvement of workforce competencies, particularly in the field of digital construction. One of the technologies widely implemented in modern construction projects is Building Information Modeling (BIM), which enables integrated planning, design, and project management. However, the understanding and application of BIM among vocational high school (SMK) students, especially those majoring in Building Engineering, remain limited. This Community Service Program (PKM) aims to enhance students’ digital construction competencies through the introduction and implementation of BIM-based learning. The program was conducted through training sessions, software demonstrations, hands-on practice, and mentoring activities focused on basic BIM applications in building design and modeling. The results of the program indicate that students showed increased understanding and practical skills in operating BIM software, as well as improved awareness of digital transformation in the construction sector. Furthermore, the activity encouraged students to develop adaptive and industry-relevant competencies that support their readiness to enter the workforce. Therefore, the implementation of BIM-based training can serve as an effective strategy to improve digital construction competencies among vocational students in the Building Engineering department.